The Translation of Contemporary Drama: McCafferty’s Quietly on the Italian Stage - Randaccio, Monica (Hungarian Journal of English and American Studies, 2020)
This article explores how spatial and temporal changes are considered as key features by both drama translator scholars and translation theorists and invites reflection on translation in general and the reception of contemporary Irish drama abroad. The comparison of Owen McCafferty’s Quietly and its Italian version demonstrates how the translation/adaptation, staging, and reception of the play in Italy must be considered against the contemporary backdrop of globalization. (MR)